Lengenda Pangeran Aryo Gajah Situbondo di Kabupaten Situbondo dan Kaitannya dengan Sejarah Masyarakat - Alif Nuril Hikmah; Moh Sutomo (SOLIDARITY: Journal of Social Studies, 2021)
This article discusses the origin of Situbondo Regency. The purpose of this writing is to find out the legend of the prince of the elephant aryo king Situbondo as someone who divided the district. The methods used in this study are historical methods with heuristic stages, source criticism (external criticism and internal criticism), interpretation and historiography and also oral sources using interview techniques with the public. about. Based on the legend of Prince Situbondo, the name of Situbondo Regency originated and narna Prince Situbondo or can be called the elephant prince Situbondo, where the knowledge of the situbondo community said that Prince Situbondo never He appeared, it was because his presence in Situbondo Regency may have died. because of the defeat of his fight with Joko Jumput, so it was only marked by the discovery of an 'odheng' (headband). Prince Situbondo was found in the Area of Benchmark Village and is now the capital of Situbondo Regency.